Assistance in managing business legality in Omah Kripik Mbote - Muhammad Luthfi; Dwi Ratna Indri Hapsari (Community Empowerment, 2023)
The ability of a business to operate legally is crucial for consumer confidence as well as providing capital for network formation and expansion. However, it is common for business actors, particularly MSMEs (micro, small, and medium-sized enterprises), to operate their companies without following the law, as is the case with the Omah Kripik Mbote. This activity's goals are to strengthen the business legality framework for partners' owned business products and to give a better understanding of business law. The following activities are used to carry out Omah Kripik Mbote's business legal assistance programs: 1) dissemination of policies for handling business legality; 2) assistance in determining the needs for processing business legality; and 3) assistance in processing business legality. The outcomes of this program included the issuance of a certificate of domicile for the Omah Kripik Mbote company and an NIB with the KBLI code.